2022
DOI: 10.1186/s12877-022-02791-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with atrial fibrillation in older patients with obstructive sleep apnea

Abstract: Purpose This study sought to identify the prevalence and factors associated with atrial fibrillation (AF) in older patients with obstructive sleep apnea (OSA) in China.  Methods This was an explorative cross-sectional study. Between January 2015 and October 2017, we continuously recruited 1285 older patients with OSA who underwent overnight polysomnography from sleep centers of multiple hospitals. They were assessed using 12-lead ECG or 24-h dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…We also found higher levels of CRP and IL‐6 in OSA patients, and this may be due to the repeated hypoxemia experienced by these patients causing oxidative stress and inflammation. Indeed, released reactive oxygen species trigger the activation of nuclear factor kappa B, leading to increased production of CRP, tumor necrosis factor‐α, and IL‐6, which together with adhesion molecules lead to endothelial damage, acting as a substrate for AF 22,23 . In addition, we were also able to confirm that patients with OSA had a greater presence of interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We also found higher levels of CRP and IL‐6 in OSA patients, and this may be due to the repeated hypoxemia experienced by these patients causing oxidative stress and inflammation. Indeed, released reactive oxygen species trigger the activation of nuclear factor kappa B, leading to increased production of CRP, tumor necrosis factor‐α, and IL‐6, which together with adhesion molecules lead to endothelial damage, acting as a substrate for AF 22,23 . In addition, we were also able to confirm that patients with OSA had a greater presence of interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, released reactive oxygen species trigger the activation of nuclear factor kappa B, leading to increased production of CRP, tumor necrosis factor-α, and IL-6, which together with adhesion molecules lead to endothelial damage, acting as a substrate for AF. 22,23 In addition, we were also able to confirm that patients with OSA had a greater presence of interstitial fibrosis. Thus, inflammation and fibrosis were increased in this subgroup of patients which may lead to a higher propensity of AF, as demonstrated in several studies.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have identified elderly individuals and those with comorbidities such as HF, DM, renal failure, and reduced diastolic function as predictors of incident AF in OSA patients [ 31 , 33 , 34 ]. Our study further corroborated these findings, highlighting that advanced age, HFpEF or HFmrEF, increased LA size, elevated E/e’, and decreased LVEF are associated with a heightened risk of AF in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 122 patients (9.5%), with 7.2% having paroxysmal AF and 2.3% with persistent AF, where the prevalence of AF was significantly greater with advanced age (p<0.05). Thus, laying out the evidence that AF is particularly frequent in older patients with OSA [ 35 ].…”
Section: Reviewmentioning
confidence: 99%